2015
DOI: 10.1155/2015/509484
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Neonatal Sepsis and Implicated Pathogens: A Study from Egypt

Abstract: Prospective analytic study was conducted in NICUs of three Egyptian Neonatal Network (EGNN) participants in Mansoura Hospitals in Egypt over a period of 18 months from March 2011 to August 2012. By using EGNN 28-day discharge form, all demographic, clinical, and laboratory data were recorded and studied. During the study period, 357 neonates were diagnosed as suspected sepsis with an incidence of 45.9% (357/778) among the admitted neonates at the three neonatal intensive care units. 344 neonates (sex ratio = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
77
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(149 citation statements)
references
References 47 publications
28
77
4
Order By: Relevance
“…In this study, a male preponderance with male to female ratio of 1.3:1 was found which was in accordance with the report of (Shah et al, 2012) (1.2:1) and (Shehab El-Din et al, 2015) (1.3:1). This might be because of more number of male infants born compared to female infants born.…”
Section: All Gram Negative Bacilli Which Includessupporting
confidence: 93%
“…In this study, a male preponderance with male to female ratio of 1.3:1 was found which was in accordance with the report of (Shah et al, 2012) (1.2:1) and (Shehab El-Din et al, 2015) (1.3:1). This might be because of more number of male infants born compared to female infants born.…”
Section: All Gram Negative Bacilli Which Includessupporting
confidence: 93%
“…The most common presentation (hypotension and pallor) were significantly higher in cases when compared to controls. El-Din et al [3] found that the most common causes of admission to NICU were respiratory distress (46.7%) and pneumonia (7.8%), while Abd Elmouttaleb et al [24] detected that the most presenting signs was respiratory distress (70%).…”
Section: Discussionmentioning
confidence: 99%
“…Early onset neonatal sepsis (EOS) is a characteristic subtype of neonatal sepsis defined according to disease onset, with bacteremia or bacterial meningitis occurring at ≤72 hours in preterm neonates admitted to neonatal intensive care unit (NICU), and in term neonates in must be occurred before 7 days [2] . Sepsis is still one of the responsible etiologies of neonatal morbidity and mortality all over the world in-spite of technological developments in neonatal health care units [3] . In Egypt, the incidence of neonatal sepsis in South Sinai Governorate hospitals was 8.6% in the NICUs and mortality rate among septic neonates (sepsis fatality rate) was about 25% [4] .…”
Section: Introductionmentioning
confidence: 99%
“…[4] In Egypt, rates of neonatal sepsis (EONS) exceeding 50% especially in neonatal intensive care unit (NICU) with a mortality rate of 51% for proven EONS and 42.9% for proven LONS. [5,6,7] The lack of a well-established laboratory marker for an early diagnosis of neonatal sepsis increases the challenge for management as rapid definitive diagnosis is required. Although blood culture is the gold standard technique it has a long turnaround time (TAT) in addition to its poor positive and negative predictive values.…”
Section: Introductionmentioning
confidence: 99%